2016
DOI: 10.1016/j.acap.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Youth and Caregiver Anxiety and Asthma Care Among Urban Young Adolescents

Abstract: Objective To examine the association of adolescent asthma-related anxiety, social anxiety, separation anxiety, and caregiver asthma-related anxiety, with asthma care by urban adolescents. Methods Participants were 386 ethnic minority adolescents (mean age=12.8) with persistent asthma and their caregivers. Adolescents reported what they do to prevent asthma symptoms and to manage acute symptoms, and if they or their caregiver is responsible for their asthma care. Adolescents completed the Youth Asthma-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
3
16
1
4
Order By: Relevance
“…Our findings support previous systematic reviews and studies that show treatment adherence are often difficult for adolescents due to forgetting medication (either intentionally or unintentionally), medication being a burden, lack of knowledge about treatments, embarrassment and apathy . We also found support for previous studies that identify other self‐management issues such as the importance of communication between adolescents and HCPs, knowledge about asthma, avoiding triggers, support from family, friends, peers, and school, and anxiety and panic . Our study also adds to the existing literature issues of self‐management highlighting themes that have not been previously reported.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings support previous systematic reviews and studies that show treatment adherence are often difficult for adolescents due to forgetting medication (either intentionally or unintentionally), medication being a burden, lack of knowledge about treatments, embarrassment and apathy . We also found support for previous studies that identify other self‐management issues such as the importance of communication between adolescents and HCPs, knowledge about asthma, avoiding triggers, support from family, friends, peers, and school, and anxiety and panic . Our study also adds to the existing literature issues of self‐management highlighting themes that have not been previously reported.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, a recent study of 176 Chinese asthma patients found that age did not have a major influence on anxiety . DL PA is significantly lower in depressed compared with non‐depressed COPD patients, and anxiety is highly prevalent among asthma patients, where it is associated with more exacerbations, more hospital readmissions, and poorer asthma control . The molecular mechanisms responsible for anxiety are not well understood and might involve abnormal neural processing of stimuli .…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the burden of illness of current citizens and has shifted from physiological infections to non-communicable psychological anxiety disorders (Dye 2008). Urban experience contributes to tension-anxiety of citizens in nearly all ages from 10 to 60 years old (Dekker et al 2008, McKenzie et al 2013, Bruzzese & Klein 2016) through shaping the socioeconomic pressure, physical environment and social interactions (Galea 2011). Results from the Global Burden of Disease Study 2013 revealed that mental and substance disorders collectively accounted for 21.2% all-year life lost to disability (YLD) wherein anxiety was ranked ninth highest specific cause of YLD in both developed and developing countries (Risal et al 2016).…”
Section: Introductionmentioning
confidence: 99%